2019
DOI: 10.1002/sce.21547
|View full text |Cite
|
Sign up to set email alerts
|

Toward a practice‐based theory for how professional learning communities engage in the improvement of tools and practices for scientific modeling

Abstract: To organize for the improvement of science instruction teachers need opportunities to collaboratively learn from practice, in practice, and to engage in the revision of classroom tools. In this paper, we examine how a professional learning community (PLC), comprised of middle school teachers and researchers, worked on the improvement of Ambitious Science Teaching (AST) practices and developed instructional practices and tools supporting model‐based inquiry. This paper focuses on the first year of a 5‐year rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 50 publications
(80 reference statements)
0
5
0
3
Order By: Relevance
“…Based on teacher reflections of what they identified as areas for improvement, teachers and coaches set goals for the following week. As such, the aims and dynamics of instructional coaching sessions were similar to those of other related studies, where coaches and teachers are conjunctly and actively involved in improvement cycles of planning, teaching and reflection (Thompson et al, 2019). Using student notebooks week on week also worked as a way to monitor and follow up on the implementation of those goals, as well as the progress across the ECM activities.…”
Section: Weekly Instructional Coaching Sessionsmentioning
confidence: 64%
“…Based on teacher reflections of what they identified as areas for improvement, teachers and coaches set goals for the following week. As such, the aims and dynamics of instructional coaching sessions were similar to those of other related studies, where coaches and teachers are conjunctly and actively involved in improvement cycles of planning, teaching and reflection (Thompson et al, 2019). Using student notebooks week on week also worked as a way to monitor and follow up on the implementation of those goals, as well as the progress across the ECM activities.…”
Section: Weekly Instructional Coaching Sessionsmentioning
confidence: 64%
“…Educational staff who want to develop teachers' learning management skills for promoting learners' creativity and innovation ability should integrate all factors of creativity and innovation such as creative thinking, creative work with others, and successful developing an innovation in the development program. Furthermore, the researcher applied 5 principles of Professional Learning Community into training activities such as sharing values and vision of learning management, constructing collaborative working culture with teachers, focusing on learners' creativity and innovation skills during learning management, supporting academic leadership to teachers, and sharing learning management experiences with teachers according to practical guidelines of Prenger, Poortman & Handelzalts (2019); Thompson, Hageneh, McDonald & Barchenger (2019); Garcia & Weiss (2019) 2020) identified that the teacher should conduct their learning management for engaging learners' potential through to the learning principle such as all learners can learn by themselves through interaction with others and appropriate environment, learning is generated from the existing knowledge that assimilation and accommodation, interaction with society will be a factor of promoting learning, practice in real life will lead to meaningful learning. In addition, teachers applied their knowledge that they received from training activities into learning management.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with this literature on preservice teacher preparation, even less literature exists on in‐service teacher learning for teaching science to MLs (see Lucas et al, 2018, for a review that addresses content areas broadly). This research will likely pick up steam with the increasing availability of NGSS‐designed educative curriculum materials and accompanying professional development (Campbell & Lee, 2021; see also J. J. Thompson et al, 2019; and Kang & Nation, 2022, for examples of professional learning centered on equity for minoritized students broadly). In this section, we highlight our emerging research on learning to teach science to MLs with two teacher populations: (a) preservice teacher education and (b) in‐service teacher education.…”
Section: Emerging Research In Science Education With Mlsmentioning
confidence: 99%